Preparticipation cardiovascular screening among National Collegiate Athletic Association Division I Institutions - Coris, E. E.; Sahebzamani, F.; Curtis, A.; Jennings, J.; Walz, S. M.; Nugent, D.; Reese, E.; Zwygart, K. K.; Konin, J. G.; Drezner, J. A. (British Journal of Sports Medicine, 2013)
Background Sudden cardiac arrest is the leading cause of death in competitive athletes during sport, and screening strategies for the prevention of sudden cardiac death are debated. The purpose of this study was to assess the incorporation of routine non-invasive cardiovascular screening (NICS), such as ECG or echocardiography, in Division I collegiate preparticipation examinations.Methods Cross-sectional survey of current screening practices sent to the head athletic trainer of all National Collegiate Athletic Association (NCAA) Division I football programmes listed in the National Athletic Trainers` Association directory.Results Seventy-four of 116 (64%) programmes responded. Thirty-five of 74 (47%) of responding schools have incorporated routine NICS testing. ECG is the primary modality for NICS in 31 (42%) of schools, and 17 (49%) also utilise echocardiography. Sixty-four per cent of the programmes that do NICS routinely screen their athletes only once as incoming freshmen. Of institutions that do not conduct NICS, American Heart Association guidelines against routine NICS and cost were the most common reasons reported.Conclusions While substantial debate exists regarding protocols for cardiovascular screening in athletes, nearly half of NCAA Division I football programmes in this study already incorporate NICS into their preparticipation screening programme. Additional research is needed to understand the impact of NICS in collegiate programmes.